Exploring Genius Loci Changes in Panembahan Yogyakarta: From Residential to Cafe Function - Vanti, Chairunisa Dwitya; Zakiyah, Zahra; Agustiananda, Putu Ayu Pramanasari; Sinaga, Bryan Putra Parsada (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2024)
This research paper aims to investigate the concept of